Trauma cinema : documenting incest and the Holocaust - Walker, Janet, 1955- (University of California Press, 2005)
Trauma Cinema focuses on a new breed of documentary films and videos that adopt catastrophe as their subject matter and trauma as their aesthetic. Incorporating oral testimony, home-movie footage, and documentary reenactment, these documentaries express the havoc trauma wreaks on history and memory. Janet Walker uses incest and the Holocaust as a double thematic focus and fiction films as a point of comparison. Her astute and original examination consid.
Keywords: Documentary films -- History and criticism.; Holocaust, Jewish (1939-1945), in motion pictures.; Incest in motion pictures.; Psychic trauma in motion pictures.; Memory.; Memory; Documentaires -- Histoire et critique.; Holocauste, 1939-1945, au cinéma.; Inceste au cinéma.; Traumatisme psychique au cinéma.; Mémoire.; memory (psychological concept); PERFORMING ARTS -- Film -- General.; Documentary films; Holocaust, Jewish (1939-1945) in motion pictures; Incest in motion pictures; Psychic trauma in motion pictures; Dokumentarfilm; Inzest -- Motiv; Judenverfolgung -- Motiv; Psychisches Trauma -- Motiv; Judenvernichtung -- Motiv; Criticism, interpretation, etc.